THE MANAGEMENT OF CHANGES IN SCHOOL - LANCARIC, Drahoslav; FRATEROVA, Zuzana (Trends in education, 2008)
The authors refer in the beginning of the article to the penetration of the management of changes necessity to the area of education. In the following text they focus on chosen differences between management of changes in the educational organizations and the management of changes in the market oriented organizations.
Keywords: management of changes; school; education.